2012
DOI: 10.1517/14728222.2013.740012
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 as a target for head and neck cancer therapy

Abstract: MMP-2 has long been a drug target. The current status of MMP-2 inhibitors as anticancer agents and their failure in the clinic is discussed in light of new data on the MMP-2s role as a cell surface transducer - data that may lead to the design and development of novel, MMP-2-targeting inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 110 publications
3
87
0
Order By: Relevance
“…MMP-2, which is a zinc-dependent proteinase, is associated with the progression, invasion and metastasis of squamous cell carcinoma, and is a potential prognostic indicator of this type of cancer (30,31). In the present study, rAd/p53 treatment exhibited a strong inhibitory effect on MMP-2 expression levels and the expression of these two genes demonstrated a negative correlation.…”
Section: A B C Dsupporting
confidence: 51%
“…MMP-2, which is a zinc-dependent proteinase, is associated with the progression, invasion and metastasis of squamous cell carcinoma, and is a potential prognostic indicator of this type of cancer (30,31). In the present study, rAd/p53 treatment exhibited a strong inhibitory effect on MMP-2 expression levels and the expression of these two genes demonstrated a negative correlation.…”
Section: A B C Dsupporting
confidence: 51%
“…Among these proteases, MMP-2 has been reported to be significantly correlated with the invasion and metastasis of human cancers, as evidenced by many studies which showed that inhibiting the expression of MMP-2 can suppress the invasion and metastasis of cancer cells (Bjorklund et al, 2005;Masson et al, 2006;Yang et al, 2013aYang et al, , 2015. For head and neck cancers, an inhibition of MMP-2 activity or synthesis also reportedly results in the suppression of metastasis of these tumors (Rosenthal et al, 2006;Chien et al, 2013). With regards to the pathogenesis of NPC, its association with MMP-2 is supported by a molecular epidemiological study which showed that the MMP-2 -1306C/T promoter polymorphism was associated with an increased risk of NPC, and enzyme linked immunosorbant assay studies which have shown that a high level of MMP-2 is associated with poor survival and high incidence of lymph node metastasis in these patients (Wong et al, 2004;Shao et al, 2011;Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most MMPs have been implicated in the tumorigenesis of various human malignancies (Chien et al, 2013;Yang et al, 2016). Among these proteases, MMP-2 has been reported to be significantly correlated with the invasion and metastasis of human cancers, as evidenced by many studies which showed that inhibiting the expression of MMP-2 can suppress the invasion and metastasis of cancer cells (Bjorklund et al, 2005;Masson et al, 2006;Yang et al, 2013aYang et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of OSCC is a multistep process requiring the accumulation of multiple genetic alterations, affected by a patient's genetic predisposition and by environmental influences, including alcohol and tobacco consumption, betel-quid chewing, chronic inflammation, and viral infection [1][2][3][4][5][6]. Expression of a gene may be affected by a single-nucleotide polymorphism (SNP) located within the promoter or other regulatory regions of the gene, and the production or activity of its translated protein is further modulated.…”
Section: Introductionmentioning
confidence: 99%